ANALYSIS OF PHYSICAL CONDITIONS OF DEGREES ATLET AT UNESA - YOGA, URI PRATAMA; Kafrawi, Fatkur Rohman (Jurnal Kesehatan Olahraga, 2019)
Abstract The physical condition of SME athletes fighting degrees at UNESA in each match is easy to experience fatigue, especially in the final round, such as running out of breath, swinging blows, and kicks under the belt. The purpose of this study was to determine the level of physical condition of athletes fighting degrees at UNESA. The target of this study was 8 UKM athletes fighting for UNESA degrees. The research was conducted around GOR BIMA and the Oentoeng Poedjadi athletic field in Surabaya State University. The research instruments used in this study were 30m Running Test to measure speed,test Shuttle Run 40m to measure agility,Test Sit-Up 30-secondto measure abdominal muscle strength,Test Sit and Reach to measure flexibility,Test Vertical Jump to measure explosive power leg muscles,Test Push-Up 1 minute to measure the endurance of arm muscles, and Multistage Fitness Test to measure the endurance of the heart and breathing. The results of a series of tests on the physical condition of UNESA combat athletes compared with the physical condition data of JATIM PON athletes showed that  athletes with, tests Shutle Run UNESA degree fighters have an average of 14.02 "moderate" categories and JATIM PON athletes have an average of 13.33 "good" categories, Test Sit Up 30 seconds UNESA fighters have an average of 51.75 "moderate" categories and JATIM PON athletes have an average of 52.6 "moderate" categories, tests for Sit and Reach UNESA degree athletes have an average of 18 "moderate" categories and JATIM PON athletes has an average of 36.7 categories "very good", The 30 m Sprint test at UNESA level athletes has an average of 4.91 "less" categories and JATIM PON athletes have an average of 4.36 categories "moderate. Test Sit Up 1 minute UNESA level athletes have an average of 54.63 categories "very good" and JATIM PON athletes have an average of 60.7 categories "very good", tests of Vertical Jump UKM UNESAhave an average of  fighters43.6250 in the category Medium, Test Push-Up to 1 minute up to UNESA level athletes have an average of 53.62 in the "moderate" category and JATIM PON athletes have an average of 60.7 "good" categories, Multistage Fitnes Test for UNESA level athletes has an average of 47.16 "good" categories and JATIM PON athletes have an average of 53.61 categories "very good",  the conclusion of this study that the level ofcondition physicalof UKM athletes fighting degrees in Surabaya State University is in the medium category with a percentage of 50% of the results of the overall component of the physical condition of UKM athletes fighting degree at Surabaya State University. Keywords: Physical Condition, Tarung Derajat